(untitled) (Jurnal Lemhannas RI, 2024)
Purpose: This article aims to identify the current state of Low-Carbon Development (LCD) within Indonesia’s poultry sector, outline the challenges encountered, and explore strategic measures to enhance its implementation in support of the green economy. Design/Methodology/Approach: This study adopts a descriptive-analytical method with a qualitative approach. Analytical tools such as PESTLE, SWOT, and the National Resilience approach are employed to assess the challenges, opportunities, and strategies for implementing LCD. Findings: Although various policies have been implemented, including the use of biodigester technology and government incentives, significant barriers persist, such as high operational costs, technological limitations, and inadequate education. Stronger policy support, financial incentives, and cross-sector collaboration are essential for a successful transition towards a green economy. Originality/Value: This article provides a comprehensive perspective on how Indonesia’s poultry sector can overcome LCD challenges by leveraging modern technology and fostering cross-sector collaboration